Analisis Pronomina dalam Cerpen-Cerpen Karya Yoga Zen di Media Sastra Digital Ruang Sastra - Indah Sulmayanti; Tiwi Indriyani; Yunita Puspita Sari; Selly Marcella (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
This research is motivated by the importance of studying pronouns in literary works because pronouns play a role in building cohesion and the meaning of stories. This research aims to describe the form and function of pronouns in the short stories Thank You for Today, Sad Stories on Sunday 4.0, and Uncle Gordi by Yoga Zen in the digital media of Ruang Sastra. This study uses a qualitative descriptive method with a morphological approach. The data source was in the form of three short stories by Yoga Zen, while the research data was in the form of words containing pronouns. The data collection technique is carried out through reading, listening, and recording techniques. The results of the study showed the existence of persona pronouns, pointer pronouns, and questioner pronouns. Persona pronouns include first, second, and third personas in the singular or plural. Pointer pronouns include general pointers, places, and concerns, while questioner pronouns include questioners people, causes, places, and circumstances. The use of pronouns in the three short stories serves to build story cohesion, strengthen the storytelling point of view, and describe the psychological condition of the characters.